1981
DOI: 10.1071/bi9810239
|View full text |Cite
|
Sign up to set email alerts
|

Hypothalamic-Pituitary Function in Normal Ewes and Ewes which Grazed Oestrogenic Subterranean Clover for Several Years

Abstract: Plasma luteinizing hormone (LH) concentrations were measured in normal Merino ewes and in Merino ewes with lowered fertility which had resulted from prolonged grazing of Trifolium subterraneum L. cv. Dinninup. During the anoestrous season, LH was measured at frequent intervals before and following administration of oestradiol-17 P or gonadotrophin releasing hormone (GnRH), and around the time of spontaneous oestrus.All ewes responded to GnRH treatment and there were no differences between the two groups in ter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
9
0

Year Published

1983
1983
2012
2012

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 17 publications
1
9
0
Order By: Relevance
“…This confirms the findings of Findlay et al (1973), and suggests that Rodgers et al (1980) and Charnley et al (1981) did not find this effect because they used entire ewes. Basal levels of LH are higher in entire affected ewes than in controls during anoestrus (Rodgers et al 1980;Charnley et al 1981), but not in ovariectomized ewes. The higher basal values indicate an altered physiological state in the entire affected ewes, which may explain why they give a greater LH response to oestradiol than occurs when both groups have a similar basal level of LH.…”
Section: Discussionsupporting
confidence: 80%
See 2 more Smart Citations
“…This confirms the findings of Findlay et al (1973), and suggests that Rodgers et al (1980) and Charnley et al (1981) did not find this effect because they used entire ewes. Basal levels of LH are higher in entire affected ewes than in controls during anoestrus (Rodgers et al 1980;Charnley et al 1981), but not in ovariectomized ewes. The higher basal values indicate an altered physiological state in the entire affected ewes, which may explain why they give a greater LH response to oestradiol than occurs when both groups have a similar basal level of LH.…”
Section: Discussionsupporting
confidence: 80%
“…Failure of positive feedback on LH is the primary cause of the permanent infertility in the 'androgenized' rat. In contrast, the entire clover-affected ewe can fully compensate for the defects in both behavioural responsiveness and the sensitivity of positive feedback, so that the duration of oestrus is normal in affected ewes (Lightfoot et al 1974) and the surge of LH occurs normally (Rodgers et al 1980;Charnley et al 1981). As discussed above, the method by which the entire ewe compensates is unclear.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…Anderson et al (2002) have demonstrated that the seasonal decline in LH pulse frequency depends on the presence of thyroid hormones occurring in the absence of steroids during spring/ summer in ewes. Chamley et al (1981Chamley et al ( , 1985 reported that during the anoestrous season both the overall mean LH concentration and the mean basal LH concentration were significantly higher in clover-infertile ewes than in control ones. These authors concluded that the increase in LH pulse frequency after ingestion of phytoestrogens might occur due to changes in the neuroendocrine regulation of LH secretion.…”
Section: Discussionmentioning
confidence: 96%
“…It is generally accepted that plant oestrogens interfere with the hypothalamic-pituitary-ovarian axis in sheep grazing oestrogenic pasture (e.g., Charnley et al 1981). In a review of clover disease, Marshall (1973) listed a number of physiological conditions in sheep associated with pasture oestrogens.…”
Section: Introductionmentioning
confidence: 99%